Rasio Neutrofil - Limfosit sebagai Prediktor Hasil Klinis pada Pasien dengan PPOK Eksaserbasi Akut: Tinjauan Literatur - Devi Chandra Juvitha; Ni Komang Ayu Swanitri Wangiyana; I Gusti Agung Ayu Eka Putri Sunari (Lombok Medical Journal, 2026)
Chronic Obstructive Pulmonary Disease (COPD) is a lung disease characterized by chronic respiratory symptoms that cause progressive and persistent airflow obstruction. Numerous inflammatory markers can be used to assess the inflammatory state in COPD patients. Neutrophil-to-Lymphocyte Ratio (NLR) is an inflammatory marker that is easy and practical to examine, which is included in a complete blood count (CBC). We conducted a narrative literature review using a thematic synthesis approach on 12 articles. Five articles demonstrated that the NLR is a good predictor of mortality or death in hospitalized patients with COPD. Two articles stated that a higher NLR in COPD patients increases the likelihood of requiring intensive care (ICU), while the other five articles explained that the NLR can be a good predictor of exacerbations in COPD patients.